R&D collaboration breadth and family-firm innovation efficiency: the role of family management and generational stage - Martínez-Alonso, Rubén; Martínez-Romero, María J.; Rojo-Ramírez, Alfonso A. (Technological and Economic Development of Economy, 2023)
This paper examines the relationship between R&D collaboration breadth and innovation efficiency within family firms. Based on the socioemotional wealth approach and recognising that family firms constitute a rather heterogeneous group, we study family firms’ differences in the way of addressing the R&D collaboration breadth-innovation efficiency link, taking into account family management and the generational stage. Using a panel dataset of 424 manufacturing family firms during the 2007–2016 period, we find significant differences across family firms in the translation of gains from R&D collaboration breadth into innovation efficiency. Specifically, our findings reveal that family firms with higher levels of family management and in first generational stage weaken the R&D collaboration breadth – innovation efficiency link.First published online 13 February 2023